Koneksyon understanding the influence of Hallyu Korean pop culture among Filipino Youth through a study of how the culture is localized and manifested in the Philippines - Rey, Donna P.; Doloricon, Leonilo O. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2018)
Over the years, the influences of various nations are evident in the Filipino image. it is given factor that these certain effects highly makes the Filipino package. So the hype that comes along with the Hallyu Wave or the Korean phenomenon is not surprising anymore. But what is refreshing to this trend is the fact that despite it entering the Filipino picture for more than a decade now, the craze was given more attention making the Korean culture, especially Koreanovelas or the Korean dramas, same with the Korean Pop Music or simply called K-pop, a household reference. With its rapid growth and obvious unceasing popularity, the study aims to know and understand how Filipinos embodies or manifests their own nationalistic flavor, culture, and identity amidst the phenomena. Through immersions to different Korean related events and by conducting in-depth interviews with professionals or experts of the topic, emphasized through the Cultural Globalization, Cultural Homogenisation, Cultural Proximity and Cultural Construction theories, the researcher was able to determine that through various means Filipinos are able to greatly adapt with the Korean influence taking these effects to their advantage. benefiting from businesses such as in fashion, beauty and food to learning the foreign language to communicate better, down to attending different events such as concerts and gatherings and actually making friends - to enjoying and making their own versions of songs and dramas through covers and parodies, it is a definite conclusion that the spirit of the Korean culture is everywhere in the Philippines.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaf 96.
Keywords: Korea -- Civilization; Philippines -- Civilization -- Korean influences; Civilization -- Korean influences; Korea